Adaptive PID Speed Control Design for Permanent Magnet Synchronous Motor Drives - Jung, Jin-Woo; Leu, Viet Quoc; Do, Ton Duc; Kim, Eun-Kyung; Choi, Han Ho; Leu, Viet Quoc (My University, 2014)
This paper proposes an adaptive proportionalintegralderivative (PID) speed control scheme for permanent magnet synchronous motor (PMSM) drives. The proposed controller consists of three control terms: a decoupling term, a PID term, and a supervisory term. The first control term is employed to compensate for the nonlinear factors, the second term is made to automatically adjust the control gains, and the third one is designed to guarantee the system stability. Different from the offline-tuning PID controllers, the proposed adaptive controller includes adaptive tuning laws to online adjust the control gains based on the gradient descent method. Thus, it can adaptively deal with any system parameter uncertainties in reality. The proposed scheme is not only simple and easy to implement, but also it guarantees an accurate and fast speed tracking. It is proven that the control system is asymptotically stable. To confirm the effectiveness of the proposed algorithm, the comparative experiments between the proposed adaptive PID controller and the conventional PID controller are performed on the PMSM drive. Finally, it is validated that the proposed design scheme accomplishes the superior control performance (faster transient response and smaller steady-state error) compared to the conventional PID method in the presence of parameter uncertainties
Keywords: Research Subject Categories::TECHNOLOGY; Adaptive control, parameter uncertainties, PID control, surface-mounted permanent magnet synchronous motor (SPMSM)